Comparison of Two 12-Key Assignments on Mobile Devices - Dagiene, V.; Grigas, G.; Jevsikova, T. (Elektronika ir Elektrotechnika, 2011)
Two variants of key assignments on 12-key mobile devices for languages based on Latin script are discussed. It is shown that the variant where all letters of the alphabet of a particular language are placed in front of digits is more preferable than that where letters with diacritics are placed after digits. The investigation was conducted, using Lithuanian, Latvian and Polish alphabets as the examples. However, all the results and conclusions, presented in the paper, are valid for any Latin script language, using the alphabet with more than 26 letters of basic Latin set. Ill. 1, bibl. 15, tabl. 5 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.108.2.153